Poor Income and Unemployment as Determinants of Labour Migration: Empirical Evidence From Bangladeshi Migrant Workers in Klang, Malaysia - Uddin, Md Sayed; Mohammed, Adam Andani (International Journal of Human Resource Studies, 2022)
The present work is an empirical study of the causes of labour migration, especially, Bangladeshi temporary migrants to Malaysia. The study is based on the survey of 100 Bangladeshi migrant workers who were selected according to two stage sampling procedure. On one stage, an area where Bangladeshi workers reside was selected through random sampling procedure. On the second stage, 100 respondents were selected from the area according to purposive snowball sampling procedure. The main objective of the study is to find out the causes for migration of Bangladeshi workers to Malaysia. The majority, 66 respondents, leave their country because of poor income. These respondents had some income in their origin country but that was not sufficient to survive their needs to look after their family. It was also found that 31 respondents left the country because of unemployment. Thus, most of the Bangladeshi workers left their country due to poor income and unemployment. Finally, the study suggested that adequate measures should be taken to provide pre-departure training on job and host county’s culture to the expected migrant workers.